Isolation and Characterization of the Bioactive Compound of Piperine in Black Pepper (Piper nigrum L.) - Listantia, Nora; Bayani, Faizul (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
One of the most famous spice species that lives in the tropics is black pepper (Piper nigrum L.). The study of piperine paved the way for its development as a bioactive compound in the treatment of various diseases, this is based on the ancient healing tradition of using black pepper. Our current study aims to isolate and characterize the bioactive compound piperine in Piper nigrum L. Black pepper was extracted with ethanol using the basic soxhletation and percolation methods. The results in the study showed that the extract from the Sokhlet process was yellowish moss green, and the piperine crystal color was yellow and shaped like a needle. Thin layer chromatography (TLC) results were observed using a UV-Vis spectrophotometer with different eluents and different Rf values were obtained. In addition, observations on the IR spectrum show that the piperine structure has been formed. This study provides an opportunity for a more in-depth exploration of the structure of piperine and future studies are very important to identify the potential utilization of piperine, especially as a basic material in the treatment of various diseases.